2016
DOI: 10.1051/radiopro/2015021
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon concentration and gamma dose rate in dwellings of the Province of Naples, South Italy, and estimation of the effective dose to the inhabitants

Abstract: The indoor radon concentration was measured in 471 dwellings in the Province of Naples. Radon concentration measurements were carried out using LR-115 passive alpha track detectors (SSNTDs) that were exposed for two consecutive semesters. The annual average radon concentration in the dwellings was found to vary from 21 to 722 Bq m −3 with an average value of 107 ± 75 Bq m −3 . In about 93% of the dwellings the radon concentrations were found to be below 200 Bq m −3 , which is the recommended level by Italian l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…0.2 to 0.5. These values are compatible with the uncertainties computed from previous concentration surveys in the Campania region [4,7]. In Fig.…”
Section: Simulated Radon Concentration Datasetsupporting
confidence: 92%
See 1 more Smart Citation
“…0.2 to 0.5. These values are compatible with the uncertainties computed from previous concentration surveys in the Campania region [4,7]. In Fig.…”
Section: Simulated Radon Concentration Datasetsupporting
confidence: 92%
“…In general, the outdoor radon concentrations are very low, while in confi ned environments, due to low ventilation, the concentration harmfully increases leading to a considerable health risk [3,4]. Moreover, in confi ned environments, other factors can contribute to increase the radon concentration, such as the emanation from building materials, the fl oor, and the degassing from tap water having a groundwater origin [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest measured value was 0.11 μSv/hour and the highest 0.31 μSv/hour, while the arithmetic mean was found to be 0.21 ± 0.04 μSv/hour (see also Fig.2 for the histogram of the measured gamma dose rates). The main source of indoor gamma radiation is the building materials and the materials lining the walls and floors of the rooms [6], however, in this research, no significant difference was found for different types of building material used in the tested environments.…”
Section: Resultscontrasting
confidence: 59%
“…In studies carried out in previous years [9][10][11][12][13], there has been a significant loss of detectors. In the publications of works, this data has not been reported; however, the outgoing and picked-up detectors have been recorded in an internal register.…”
Section: Resultsmentioning
confidence: 99%